2023
DOI: 10.1111/cns.14132
|View full text |Cite
|
Sign up to set email alerts
|

β‐Glucan attenuates cognitive impairment of APP/PS1 mice via regulating intestinal flora and its metabolites

Abstract: Background The intestinal flora has been shown to be involved in the progression of Alzheimer's disease (AD) and can be improved by β‐glucan, a polysaccharide derived from Saccharomyces cerevisiae, which affects cognitive function through the intestinal flora. However, it is not known if this effect of β‐glucan is involved in AD. Method This study used behavioral testing to measure cognitive function. After that, high‐throughput 16 S rRNA gene sequencing and GC–MS were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 80 publications
(142 reference statements)
0
2
0
Order By: Relevance
“…31 Romboutsia was increased in the spleen-qi deficiency model group, and Romboutsia with high abundance was also found in the intestinal flora of Alzheimer's disease patients. 32,33 It can be concluded that the intestinal microbiota structure of rats with spleen-qi deficiency syndrome changes significantly, which affects intestinal metabolism and body immunity, and will promote the development of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…31 Romboutsia was increased in the spleen-qi deficiency model group, and Romboutsia with high abundance was also found in the intestinal flora of Alzheimer's disease patients. 32,33 It can be concluded that the intestinal microbiota structure of rats with spleen-qi deficiency syndrome changes significantly, which affects intestinal metabolism and body immunity, and will promote the development of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…299,300 Moreover, probiotic and prebiotic interventions aimed at elevating SCFA levels have demonstrated neuroprotective effects in AD mouse models by inhibiting glial activation and Aβ deposition. [301][302][303][304][305][306] Elevating butyrate through probiotic intervention (Clostridium butyricum) has been shown to inhibit microglial activation and reduce the levels of levels pro-inflammatory cytokines in APP/PS1 mice. Furthermore, butyrate exerts anti-inflammatory effects by downregulating the levels of cyclooxygenase-2 (COX-2) and CD11b, and suppressing NF-κB signaling in Aβ-induced BV-2 cells.…”
Section: Gut Microbiota-derived Metabolites In Neurodegenerative Dise...mentioning
confidence: 99%